Ethnic differences in disability prevalence and their determinants studied over a 20-year period: a cohort study. - Emily D Williams; Therese Tillin; Peter Whincup; Nita G Forouhi; Nishi Chaturvedi (PLoS ONE)
Background To compare disability prevalence rates in the major ethnic groups in the UK and understand the risk factors contributing to differences identified. It was hypothesised that Indian Asian and African Caribbean people would experience higher rates of disability compared with Europeans. Methods Data was collected from 888 European, 636 Indian Asian and 265 African Caribbean men and women, aged 58-88 years at 20-year follow-up of community-based cohort study, based in West London. Disability was measured using a performance-based locomotor function test and self-reported questionnaires on functional limitation, and instrumental (IADL) and basic activities of daily living (ADL). Results The mean (SD) age of participants at follow-up was 69.6 (6.2) years. Compared with Europeans, Indian Asian people were significantly more likely to experience all of the disability outcomes than Europeans; this persisted after adjustment for socioeconomic, behavioural, adiposity and chronic disease risk factors measured at baseline (locomotor dysfunction: adjusted odds ratio (OR) 2.20, 95% CI 1.56-3.11; functional limitation: OR 2.77, 2.01-3.81; IADL impairment: OR 3.12, 2.20-4.41; ADL impairment: OR 1.58, 1.11-2.24). In contrast, a modest excess risk of disability was observed in African Caribbeans, which was abolished after adjustment (e.g. locomotor dysfunction: OR 1.37, 0.90-1.91); indeed a reduced risk of ADL impairment appeared after multivariable adjustment (OR from 0.99, 0.68-1.45 to 0.59, 0.38-0.93), compared with Europeans. Conclusions Substantially elevated risk of disability was observed among Indian Asian participants, unexplained by known factors. A greater understanding of determinants of disability and normative functional beliefs of healthy aging is required in this population to inform intervention efforts to prevent disability.